PENCAIRAN BATUBARA BANKO TENGAH TANPA KATALIS - Neny Rochyani (Jurnal Media Teknik, 2005)
Abstract      Coal liquefaction is a process which to convert the energy in solid organic structure into liquid form. This process appear just because a petroleum reserve more lessen. As  the country that have coal reserve in a large amount. The process of liquefaction development as the potensial alternative will have the benefit for us. The goal of this research is to know how much the conversion result from Banko Tengah coal liquefaction in temperature of 425°C by using antrasent solvent. The main equipment appliance of this research is autoclave that have 0,5 litre capacities, which emited a stream by gas H2, the comparation ratio of solvent /coal = 3 :2, pressure 100 bar. Based on the result shows that in 75 minute produced a highest conversions in the mount of 65,4696 %.  Abstrak           Pencairan batubara adalah suatu proses untuk mengkonversikan energy yang tersimpan dalam struktur organic padat batubara kedalam bentuk cair. Proses ini muncul karena semakin berkurangnya cadangan minyak bumi. Sebagai negara yang mempunyai cadangan batubara dalam jumlah besar, pengembangan proses pencairan sebagai bahan bakar alternative yang potensial akan sangat menguntungkan . penelitian ini bertujuan untuk mengetahui besarnya hasil konversi pencairan batubara Banko tengah pada temperature 425 C dengan menggunakan pelarut atrasen. Alat utama dalam penelitian ini adalah autoclave berkapasitas 0,5 liter yang adialiri gas H2 rasio perbandingan berat pelarut/batubara = 3 :2, tekanan 100 bar. Dari hasil percobaan menunjukkan bahawa pada waktu operasi 75 menit dihasilkan konversi sebesar 65,4696 %.